Potensi Ekstrak Tanaman sebagai Antibakteri terhadap Vibrio parahaemolyticus: Sebuah Tinjauan Pustaka - Anisa, Hosia; Amin, Muhamad; Mukti, Akhmad Taufiq; Mahasri, Gunanti (Jurnal Perikanan Unram, 2025)
Aquaculture faces serious threats, one of which is infectious disease caused by Vibrio parahaemolyticus bacteria. These bacteria have shown antibiotic resistance and cause significant economic losses. The need for safe and sustainable antibacterial alternatives is crucial given the negative impact of using synthetic antibiotics. This review explores the potential of Shorea beccariana, Uncaria gambir, and Swietenia macrophylla as natural antibacterial agents against Vibrio parahaemolyticus. A systematic descriptive study method was used to integrate primary literature. Results showed that V. parahaemolyticus is a pathogenic Gram-negative bacterium with a complex virulence mechanism. Various studies have confirmed the antibacterial activity of plant secondary metabolites, such as flavonoids, tannins, and terpenoids, against Vibrio spp. Although the specific effectiveness of these three plants against V. parahaemolyticus has not been widely studied, the bioactive compounds identified in their extracts show strong potential. These compounds work by damaging the integrity of bacterial cells and disrupting their metabolism, offering a promising natural solution for vibriosis control.